PEMANFAATAN RADIASI ENERGI TEGANGAN 150 KV UNTUK LAMPU LED PENERANGAN JALAN - Mauludi Manfaluthy (Universitas Muhammadiyah Tangerang, 2018)
WHO (World Health Organization) concludes that not much effect is caused by electric field up to 20 kV / m in humans. WHO standard also mentions that humans will not be affected by the magnetic field under 100 micro tesla and that the electric field will affect the human body with a maximum standard of 5,000 volts per meter. In this study did not discuss about the effect of high voltage radiation SUTT (High Voltage Air Channel) with human health. The research will focus on energy utilization of SUTT radiation. The combination of electric field and magnetic field on SUTT (70-150KV) can generate electromagnetic (EM) and radiation waves, which are expected to be converted to turn on street lights around the location of high voltage areas or into other forms. The design of this prototype works like an antenna in general that captures electromagnetic signals and converts them into AC waves. With a capacitor that can store the potential energy of AC and Schottky diode waves created specifically for low frequency waves, make the current into one direction (DC). From the research results obtained the current generated from the radiation is very small even though the voltage is big enough.Keywords : Radiance Energy, Joule Thief, and LED Module.